Molecular Dynamics Simulations of Nucleic Acids. From Tetranucleotides to the Ribosome - Šponer, Jiří; Banáš, Pavel; Jurečka, Petr; Zgarbová, Marie; Kührová, Petra; Havrila, Marek; Krepl, Miroslav; Stadlbauer, Petr; Otyepka, Michal (The journal of physical chemistry letters, 2014)
We present a brief overview of explicit solvent molecular dynamics (MD) simulations of nucleic acids. We explain physical chemistry limitations of the simulations, namely, the molecular mechanics (MM) force field (FF) approximation and limited time scale. Further, we discuss relations and differences between simulations and experiments, compare standard and enhanced sampling simulations, discuss the role of starting structures, comment on different versions of nucleic acid FFs, and relate MM computations with contemporary quantum chemistry. Despite its limitations, we show that MD is a powerful technique for studying the structural dynamics of nucleic acids with a fast growing potential that substantially complements experimental results and aids their interpretation.